2007
DOI: 10.2522/ptj.20060066
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Prediction Rule to Identify Patients With Knee Pain and Clinical Evidence of Knee Osteoarthritis Who Demonstrate a Favorable Short-Term Response to Hip Mobilization

Abstract: Background and Purpose: The primary purpose of this study was to develop a clinical prediction rule (CPR) for identifying patients with knee pain and clinical evidence of knee osteoarthritis (OA) with favorable short-term response to hip mobilizations. The secondary purpose was to determine the predictive validity of individual clinical tests for identifying these same patients.Subjects and Methods: Sixty subjects with knee OA, aged 51 to 79 years, completed self-report questionnaires, a clinical examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 39 publications
(21 reference statements)
1
34
1
Order By: Relevance
“…Although causality cannot be inferred from cross-sectional data, it is possible that addressing hip ROM deficits that fall below the breakpoints would improve function, which is reminiscent of the substantial functional improvements associated with hip joint mobilizations demonstrated by Hoeskma et al (18) and Currier et al (47). Interestingly, although Hoeskma et al (48) did not identify patient subgroups for whom mobilizations would be most beneficial, the clinical criteria used to diagnose hip OA in their study included less than 115°and 15°for hip flexion and internal rotation, respectively (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although causality cannot be inferred from cross-sectional data, it is possible that addressing hip ROM deficits that fall below the breakpoints would improve function, which is reminiscent of the substantial functional improvements associated with hip joint mobilizations demonstrated by Hoeskma et al (18) and Currier et al (47). Interestingly, although Hoeskma et al (48) did not identify patient subgroups for whom mobilizations would be most beneficial, the clinical criteria used to diagnose hip OA in their study included less than 115°and 15°for hip flexion and internal rotation, respectively (49).…”
Section: Discussionmentioning
confidence: 99%
“…Because these values fell below our breakpoints, one would expect most, if not all, of their patients to benefit from hip joint mobilizations. Equally, Currier et al (47) found that individuals with symptomatic hip OA and hip internal rotation of less than 17°tended to respond favorably to hip mobilizations. Again, because the ROM was below our breakpoint, their results match our expectations.…”
Section: Discussionmentioning
confidence: 99%
“…A GROC score of z3 has previously been used as the criterion to determine a favorable response to manual physical therapy interventions. 54 A 2.0-point change in the NPRS has been reported to be clinically meaningful. 55 While there is currently no estimate of the minimal clinically meaningful difference for elbow extension ROM during the ULNT, it has been reported that differences greater than 7.5u represent true (non-error) differences.…”
Section: Discussionmentioning
confidence: 99%
“…Th e rules are algorithmic in nature and involve condensed information that identifi es the smallest number of indicators that are statistically diagnostic to the targeted condition 6 . Th e number of derived or validated CPRs is increasing 6 , specifi cally in rehabilitation medicine where prescriptive studies have been developed for musculoskeletal interventions for low back pain 7,8 , cervical pain 9,10 , and knee dysfunction 11,12 . Clinical prediction rules may best be classifi ed into three distinct groups: 1) diagnostic, 2) prognostic, and 3) prescriptive 1,13 .…”
Section: What Are Clinical Prediction Rules?mentioning
confidence: 99%